2007
DOI: 10.1038/nprot.2007.155
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of high-throughput in vitro protein phosphatase screening assays

Abstract: We describe here detailed protocols to design, optimize and validate in vitro phosphatase assays that we have utilized to conduct high-throughput screens for inhibitors of dual-specificity phosphatases: CDC25B, mitogen-activated protein kinase phosphatase (MKP)-1 and MKP-3. We provide details of the critical steps that are needed to effectively miniaturize the assay into a 384-well, high-throughput format that is both reproducible and cost effective. In vitro phosphatase assays that are optimized according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…The activity of VHR phosphatase was measured using the substrate 3-Omethylfluorescein phosphate (OMFP; Sigma) in a 96-well microtiter plate assay based on methods described previously. 17 The NSC-87877 (Calbiochem) and OMFP were solubilized in H2O and DMSO, respectively. All reactions were performed at a final concentration of 1% DMSO.…”
Section: Notesmentioning
confidence: 99%
“…The activity of VHR phosphatase was measured using the substrate 3-Omethylfluorescein phosphate (OMFP; Sigma) in a 96-well microtiter plate assay based on methods described previously. 17 The NSC-87877 (Calbiochem) and OMFP were solubilized in H2O and DMSO, respectively. All reactions were performed at a final concentration of 1% DMSO.…”
Section: Notesmentioning
confidence: 99%
“…An initial drawback of OMFP was that the commercially available form is the cyclohexylammonium salt, which has very poor solubility in many organic solvents (including DMSO), requiring sonication to prepare stock solutions. 48 However, we found that this can be easily overcome by making stocks with an acidified organic solvent, thereby forming the, quite soluble, OMFP free acid (see ''Materials and Methods'' section). An examination of the reaction progress curves for an enzyme and substrate provides a basis for choosing appropriate conditions for the biochemical screening assay: concentrations of substrate and enzyme, and length of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatase activity was measured using the substrate OMFP (Sigma-Aldrich, St. Louis, MO) in a 96-well microtiter plate assay based on methods described previously. 17 PTP inhibitor V and OMFP were solubilized in dimethyl sulfoxide (DMSO). All reactions were performed at the final concentration of Figure 2.…”
Section: Methodsmentioning
confidence: 99%